2019
DOI: 10.1016/j.neuroscience.2018.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Gene and Protein Expression in the Non-human Primate Central Extended Amygdala

Abstract: Alterations in central extended amygdala (EAc) function have been linked to anxiety, depression, and anxious temperament (AT), the early-life risk to develop these disorders. The EAc is composed of the central nucleus of the amygdala (Ce), the bed nucleus of the stria terminalis (BST), and the sublenticular extended amygdala (SLEA). Using a non-human primate model of AT and multimodal neuroimaging, the Ce and the BST were identified as key AT-related regions. Both areas are primarily comprised of GABAergic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Because of this bridging role, the SLEA is implicated in stress-induced behavior (Fudge et al, 2017) relevant for fear memory processes. Notably, the SLEA is thought to contribute to the instantiation of fear and anxiety states (Kovner et al, 2019;Shackman & Fox, 2016;Tillman et al, 2018), thus playing a central role in the evaluation of potentially threat-related information. Additionally, the SLEA assists in the preparation of threat-related defensive responses (Oler et al, 2017;Shackman & Fox, 2016).…”
Section: The Slea and Threat-related Responses In Ptsd + Ds Patient Groupmentioning
confidence: 99%
“…Because of this bridging role, the SLEA is implicated in stress-induced behavior (Fudge et al, 2017) relevant for fear memory processes. Notably, the SLEA is thought to contribute to the instantiation of fear and anxiety states (Kovner et al, 2019;Shackman & Fox, 2016;Tillman et al, 2018), thus playing a central role in the evaluation of potentially threat-related information. Additionally, the SLEA assists in the preparation of threat-related defensive responses (Oler et al, 2017;Shackman & Fox, 2016).…”
Section: The Slea and Threat-related Responses In Ptsd + Ds Patient Groupmentioning
confidence: 99%
“…In patients with IBS, several brain regions responsible for the modulation of the hypothalamic-pituitary-adrenal (HPA) axis, such as the central extended amygdala, thalamus, and prefrontal cortex, are associated with emotional arousal, endogenous pain modulation, and gastrointestinal hyperactivity ( Berman et al, 2008 ; Price, 2003 ; Tillisch et al, 2011 ; Wilder-Smith, 2011 ). In support of these clinical observations, our prior research in experimental models has demonstrated that the anterior ventral bed nucleus of the stria terminalis (avBNST), a critical node of the central extended amygdala, is a vital structure for mediating visceral nociception with the activation of HPA axis in the stressful condition ( Kovner et al, 2019 ; Yu et al, 2020 ). Here, we focused on another important node of the central extended amygdala, the anterior lateral bed nucleus of the stria terminalis (alBNST), to fully explore the role of the entire central extended amygdala in chronic visceral pain.…”
Section: Introductionmentioning
confidence: 90%
“…Crf and Cck are non-overlapping GABAergic subpopulations that occupy separate lateral vs. medial subdivisions, co-residing in adjacent compartments throughout the middle of the BNST A/P axis, approximately +0.2 to −0.2 mm from Bregma in the mouse. In addition to Crf and Cck , the neuropeptides dynorphin ( Pdyn ), enkephalin ( Penk ), neurotensin ( Nts ), neuropeptide Y ( Npy ), nociceptin ( Pnoc ), somatostatin ( Sst ), substance P ( Tac1 ), neurokinin B ( Tac2 ), and vasopressin ( Avp ) are also found in neurons throughout the BNST (Malsbury and McKay, 1987 ; Walter et al, 1991 ; Poulin et al, 2009 ; Kudo et al, 2014 ; Crowley et al, 2016 ; Ahrens et al, 2018 ; Giardino et al, 2018 ; Zelikowsky et al, 2018 ; Kovner et al, 2019 ; Rigney et al, 2019 ; Rodriguez-Romaguera et al, 2020 ; Smith et al, 2020 ; Whylings et al, 2020 ; Xiao et al, 2020 ; Figure 1A ). Labeling for the calcium-binding protein calretinin appears selective for the dorsolateral (dl)BNST, whereas dopamine receptor type-1 ( Drd1 ) and protein kinase C delta ( Pkcd ) neurons cluster more specifically within the oval nucleus (ovBNST, a discrete subnucleus within the larger dlBNST subregion; Kim et al, 2013 ; Nguyen et al, 2016 ; Pomrenze et al, 2019a ; Wang et al, 2019 ).…”
Section: Molecularly-defined Bnst Cell Typesmentioning
confidence: 99%